2013
DOI: 10.1371/journal.pone.0062515
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Dopaminergic Modulation to Motor Cortical Plasticity between Parkinson's Disease and Multiple System Atrophy

Abstract: Dopamine modulates the synaptic plasticity in the primary motor cortex (M1). To evaluate whether the functioning of the cortico-striatal circuit is necessary for this modulation, we applied a paired associative stimulation (PAS) protocol that comprised an electric stimulus to the right median nerve at the wrist and subsequent transcranial magnetic stimulation of the left M1, to 10 patients with Parkinson's disease (PD) and 10 with multiple system atrophy of the parkinsonian type (MSA-P) with and without dopami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 51 publications
0
21
1
Order By: Relevance
“…Therefore our results challenge the classical view of generally reduced sensorimotor cortical plasticity in PD . We show that enhanced response to PAS in PD may be detected when clinical signs are minimal, becoming less pronounced with worsening of motor signs.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Therefore our results challenge the classical view of generally reduced sensorimotor cortical plasticity in PD . We show that enhanced response to PAS in PD may be detected when clinical signs are minimal, becoming less pronounced with worsening of motor signs.…”
Section: Discussioncontrasting
confidence: 60%
“…Therefore our results challenge the classical view of generally reduced sensorimotor cortical plasticity in PD. 32, [34][35][36][37][38] We show that enhanced response to PAS in PD may be detected when clinical signs are minimal, becoming less pronounced with worsening of motor signs. In PD, motor symptoms emerge only after a prolonged period of dompaminergic loss, on account of activity of adaptive or compensatory mechanisms.…”
Section: Cortical Plasticitymentioning
confidence: 75%
“…Plasticity in atypical parkinsonism has also been tested using PAS and TBS protocols. There is one report of absent responses to PAS in MSA‐P patients both on and off l ‐dopa . In PSP, cTBS causes MEP facilitation instead of inhibition, and iTBS induces greater MEP facilitation when compared with healthy individuals .…”
Section: Methodsmentioning
confidence: 99%
“…There is one report of absent responses to PAS in MSA-P patients both on and off L-dopa. 89 In PSP, cTBS causes MEP facilitation instead of inhibition, 70 and iTBS induces greater MEP facilitation when compared with healthy individuals. 70 It has been suggested that the latter might result from the loss of M1 inhibitory interneurons.…”
Section: Attempts To Use Tms In Differential Diagnosismentioning
confidence: 99%
“…Neurophysiological studies in humans using transcranial magnetic stimulation (TMS) have revealed changes in resting measures of excitability and plasticity in M1. There is enhanced corticospinal excitability and reduced M1 inhibition (Cantello et al, 2002;Currà et al, 2002;Lefaucheur et al, 2005;Berardelli et al, 2008;Bologna et al, 2016b), together with reduced long-term potentiation (LTP)-like plasticity in M1 (Morgante et al, 2006;Ueki et al, 2006;Schwingenschuh et al, 2010;Suppa et al, 2011;Kojovic et al, 2012 andKawashima et al, 2013;Kishore et al, 2017).…”
Section: Introductionmentioning
confidence: 99%